Improving Oral Health of a Child: A Parent’s Guide - Debasruti Naik1, Motirmoy Giri2, Ramesh Nagarajappa2, Sudipta Sahu3, Kajal Kiran Sahu4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
For every parent, the early phase of growing a child is one of their life’s most challenging as well asresponsible experiences that can bring out the very best in us our patience and our skill to provide them goodhealth. This article will provide essential information to help out parents build knowledge about maintaininggood oral health of their children and also will help to make out the vital building blocks of parent-childrelationships. This article will also help parents reflecting their actions to better understand their children’soral health. Small children at their younger age are very sensitive to social stimuli such as praise as wellas affection and they learn best by imitating their parents. This knowledge will help parents to guide theirchildren as they grow towards handling their oral health. This article is meant for parents of children ofall ages and in all cultures which will be helpful and may provide insight to professionals like caregivers,teachers and early childhood educators.